Controle estatístico da qualidade do composto orgânico proveniente de resíduos agroindustriais - Carneiro, Leocir José (2016)
The quality of an organic compound has been measured by the variability of some variables cited by the Ministry of Agriculture, Livestock and Supply (MAPA). Thus, this trial aimed at monitoring the quality on organic compost production at Compostec company based on statistical control quality (SCQ). The company is located on 317-PR Highway, KM 06, Rural Zone in Toledo city, Paraná. The samples were collected from 01/04/2014 to 04/01/2015. There were 21 piles and from each one of them five samples were collected, so there was a total of 105 samples. The analyzed variables were: moisture, pH, electrical conductivity (EC), carbon, nitrogen, phosphorus, potassium, carbon/nitrogen ratio, cation exchange capacity (CEC), CEC/C ratio, cadmium, lead, copper and zinc. The Shewhart control chart was calculated to obtain the process capability index for each variable. The SQC was shown to be applicable to companies that produce organic compost based on composting in plowed piles. The process did not show statistical control in any of the variables analyzed, but the company can produce organic compound based on the rules and/or safe limits in relation to: moisture, pH, EC, P, K, CEC. The production process is acceptable in relation to C, N and C/N ratio, but ineffective to CEC/C ratio, Cu, Zn, Cd and Pb. The variables that best represent the compound quality and can be easily monitored with control charts are C, N and C/N ratio.